ASSESSING SOUTH AFRICA’S ECONOMIC GROWTH AND FOREIGN DIRECT INVESTMENT: IMPLICATIONS FOR ENVIRONMENTAL SUSTAINABILITY - Ahmed Tobi Adekunle (MATTER: International Journal of Science and Technology, 2025)
Environmental sustainability is essential element of the global focus based on 26th UN climate change conference, 2021. Essentially, recent rapid economic growth in South Africa (SA) has created verifying environmental sustainability. Sequel to this, this study assesses SA economic growth and Foreign Direct Investment, implications for environmental sustainability span over 1986-2022. Environmental Kuznet Hypothesis is the framework adopted for the study using ARDL techniques to assess the long-run connection amid the variables. The findings signify that rises in economic growth creates more carbon emissions, then begins to fall at a particular level, thereby confirming Environmental Kuznet Hypothesis for SA. The causality approach signifies that Foreign Direct Investment, urban population and economic growth contribute significantly to carbon emission threshold in SA. Essentially, future researchers may choose to adapt the study to Sub-Saharan Africa and incorporate one or more control variables.